Ultrasound in the Diagnosis, Monitoring, and Treatment of Retrocalcaneal Bursitis - Levent TEKİN,; Alparslan Bayram ÇARLI,; Selim AKARSU, (Archives of Rheumatology, 2013)
Musculoskeletal ultrasonography provides a significant benefit to clinics regarding time and cost.[<r1>] Additionally, a number of reviews have recommended that treatment of musculoskeletal system injuries should be performed with image guidance.[<r2>] The visualization of the needle in realtime imaging allows for the reliable placement of the needle tip in the tendon sheath, bursa, or joint of interest.[<r3>] Furthermore, some types of provocative pain measurements, such as the pressure pain threshold and visual analog scale, can also be performed during ultrasound evaluations.[<r2>] A 22-year-old female was seen for pain, swelling, and sensitivity to palpation at the posterior area of the left ankle as well as difficulty during walking. Upon detailed questioning, she stated that she had sprained her ankle two weeks prior to coming to our clinic. Laboratory evaluations, including complete blood count, erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor, uric acid, liver, and renal function tests, were all normal. An X-ray evaluation of the left ankle was not contributory. Despite nonsteroidal antiinflammatory drugs, rest, and cold application on the swollen area, the patient's symptoms persisted. Further evaluation was conducted using ultrasound, and this showed no signs of cortical bony irregularities, calcaneal spurs, plantar fasciitis, Achilles tendonitis/tendinosis, or calcification, but it did reveal fluid accumulation in the retrocalcaneal bursa. Power Doppler evaluation revealed nothing remarkable, but “sono-palpation” exacerbated her pain. In the end, the patient was diagnosed as having retrocalcaneal bursitis. Accordingly, an ultrasound guided injection of dexamethasone 2 mg/ml was performed after the fluid was aspirated. The patient's complaints decreased dramatically within two days after this injection, and repeat ultrasound revealed no pathology on the third day. Ultrasonography, a non-invasive diagnostic tool, can provide important information for the evaluation and management of patients with musculoskeletal injuries. In addition, it can assist in giving better care and a prompt diagnosis while also being beneficial for the serial follow-up of patients. With this in mind, we described a case of retrocalcaneal bursitis that was diagnosed and treated using ultrasound. We believe that every physician who treats musculoskeletal disorders can indisputably benefit from the use of ultrasound in daily clinical practice. Declaration of conflicting interests The authors declared no conflicts of interest with respect to the authorship and/or publication of this article. Funding The authors received no financial support for the research and/or authorship of this article.